Management of tracheostomy during COVID-19 outbreak: Heat and moisture exchanger filter and closed suctioning system - De Seta, Daniele (Oral Oncol, 2020)
• Precautions for safer management of tracheostomy should be taken for all patients. • HMEFs and closed endotracheal suctioning systems protect patients and healthcare professionals. • Precaution for reduce the COVID-19 diffusion should be taken until the epidemic is controlled.